Proximate composition of Lathyrus sativus (Variety Mahateora) - Lakra, Leena Preeti; Patel, S; Patel, Yashwant Kumar; Kaladhar, DSVGK; Sudhakar, Meesala; Agrawal, Nikki; Toppo, Swati Rose (Journal of Postharvest Technology, 2023)
Lathyrus sativus is one of the most important food legumes in countries like Bangladesh, India and Ethiopia. Pulses play an important role in preventing from several diseases including illness, diabetes, jaundice, cancer and heart disease. In this present study the split dhal, husk and whole seed (Lathyrus sativus) seeds were analyzed for proximate composition. The proximate composition of Lathyrus seed (split dhal) was determined and it was observed that the moisture content, protein content, fat content, total ash content, crude fiber and carbohydrate content was found to be 8.4, 22.0, 2.3, 2.90, 3.94 and 60.0% respectively. In husk, the moisture content, protein content, fat content, total ash content, crude fiber and carbohydrate content was found to be 8.6, 25.0, 2.4, 3.09, 2.26 and 59.17% respectively. In whole seed, the moisture content, protein content, fat content, total ash content, crude fiber and carbohydrate content was found to be 8.6, 28.67, 2.2, 2.86, 2.1 and 56.17 %, respectively.